Neurointerventions and the law regulating human mental capacity - Vincent, Nicole A.; Nadelhoffer, Thomas; McCay, Allan (Oxford University Press, 2020)
This volume makes a contribution to the field of neurolaw by investigating issues raised by the development, use, and regulation of neurointerventions. The broad range of topics covered in these chapters reflects neurolaw's growing social import, and its rapid expansion as an academic field of inquiry. Some authors investigate the criminal justice system's use of neurointerventions to make accused defendants fit for trial, to help reform convicted offenders, or to make condemned inmates sane enough for execution, while others interrogate the use, regulation, and social impact of cognitive enhancement medications and devices.
Also issued in print: 2020. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on May 25, 2020)
Keywords: Mental health laws; Law / Psychological aspects; Criminal psychology; Neurology / Law and legislation